Pengaruh Content Marketing dan SEO (Search Engine Optimization) Terhadap Keputusan Pembelian Melalui Minat Beli: Studi pada Konsumen Produk UKM F&B di Kabupaten Pasuruan - Indah Zanubah Khafsoh; Miftahul Huda (Economic Reviews Journal, 2024)
This study aims to analyze the relationship between Content Marketing and Search Engine Optimization (SEO) on Purchase Decisions through Buying Interest in consumers of F&B SME products in Pasuruan Regency. This study uses an explanatory research approach with data analysis techniques using path analysis.  The type of data used is quantitative data, using questionnaires as a data source. The sampling method uses purposive sampling with certain criteria. The results of this study show that: 1) The Content Marketing variable has a significant effect on the Buying Interest variable with a t-calculated value of 3.811 > 1980. 2) The Search Engine Optimization (SEO) variable has a significant effect on the Buying Interest variable with a t-count value of 7.672 > 1980. 3) The Content Marketing variable has a significant effect on the Purchase Decision variable with a t-calculated value of 3.126 > 1980. 4) The Search Engine Optimization (SEO) variable has a significant effect on the Purchase Decision variable with a t-count value of 3.841 > 1980. 5) the Buying Interest variable has a significant effect on the Purchase Decision variable with a t-calculated value of 5.439 > 1980. 6) The Content Marketing variable has a significant effect on the Purchase Decision variable through the Buying Interest variable with a t-calculated value of 3.807 > 1980. and 7) The Search Engine Optimization (SEO) variable has a significant effect on the Purchase Decision variable through the Buying Interest variable with a t-count value of 4,900 > 1980.